Influence of bismuth oxide on gamma radiation shielding properties of borotellurite glass - Mohamed Kamari, Halimah; A., Zuraidah; M., Ishak; Laoding, Hasnimulyati (Elsevier, 2019)
Boro-tellurite glasses have recently been attracting the attention of several researchers as a tremendous optical device and shielding material. In this work, boro-tellurite glasses with bismuth oxide (Bi2O3) have been synthesized by melt quenching technique. The structural and shielding property changes after adding of bismuth oxide in boro-tellurite glass were studied using Fourier Transform Infrared (FTIR) and Lead Equivalent Thickness measurement (LET), respectively. The results show that the bismuth oxide increases glass density, changes the glass structure, and increases the radiation shielding properties. Changes in the glass structure are due to atomic rearrangements and formation of non-bridging oxygen (NBO). The density of boro-tellurite glass system increased up to 97% when Bi2O3 content increased, which is due to the high molecular weight of Bi2O3 and the increasing number of NBO atoms in the glass structure. In addition, the mass attenuation coefficient of the glass system increases as Bi2O3 concentration increases and the half value layer and mean free path show that present glass better than some standard concretes and commercial radiation shielding glasses. Current results demonstrated the advantages of bismuth-boro-tellurite glass as a new candidate of gamma radiation shielding material in selected energy range.